Beliefs, Perceptions, and Behaviors Regarding Chronic Respiratory Diseases of Roma in Crete, Greece: A Qualitative FRESH AIR Study - Anastasaki, Marilena; van Bree, Egid M.; Brakema, Evelyn A.; Tsiligianni, Ioanna; Sifaki-Pistolla, Dimitra; Chatzea, Vasiliki E.; Crone, Matty C.; Karelis, Andreas; van der Kleij, Rianne M. J. J.; Poot, Charlotte C.; Reis, Ria; Chavannes, Niels H.; et al. (Frontiers in Public Health, 2022)
Background: The global burden of chronic respiratory diseases (CRDs) disproportionally affects Roma populations. Health interventions addressing CRD among Roma or other vulnerable groups often fail to be effective, as their implementation strategy misaligns with the local context. To design context-driven strategies, we studied CRD-related beliefs, perceptions, and behaviours among a Greek Roma population, focussing on asthma and COPD. Methods: For this qualitative study in Crete, Greece, we used a Rapid Assessment Process. We conducted interviews and focus groups with purposively selected Roma community members (CMs), key informants (KIs) and healthcare professionals (HPs) serving the population. Data were triangulated using observations of households and clinical consultations. Key themes were identified using Thematic Content Analysis. The Health Belief Model, the Explanatory Model of Illness, and the Theory of Planned Behaviour that are complementary is some aspects, guided our methodology with the several variables from them to be integrated to better understand CRD risk preventative behavior. Results: We conducted 6 focus groups, 7 interviews and 13 observations among 15 CMs, 4 KIs, and 3 HPs. Five themes emerged: 1) Poor CRD-awareness (smoking and household air pollution were perceived as harmful, but almost exclusively associated with acute rather than chronic symptoms); 2) Low perceived susceptibility to CRD ( and CMs tended to ignore respiratory symptoms); 3) High risk exposure (smoking was common, and air pollution was perceived inevitable due to financial constraints); 4) Healthcare seeking (healthcare was sought only for persistent, severe symptoms, daily needs were a priority); 5) Perceived barriers/facilitators to care (health illiteracy, perceived discrimination and financial constraints were main barriers; established trust the main facilitator). Conclusion: These five themes highlight that strategies to tackle CRD in the studied Roma setting require a multilevel approach: bridging awareness gaps at the population level, providing resources to enhance the adoption of healthy behaviours, and fighting discrimination at the societal level, whilst establishing trusted relationships at the local level. Similar methodologies to address local context may strengthen the implementation of effective interventions for similarly vulnerable and/or low-resource populations.